IMPLICATURE IN ENGLISH TEXTBOOKS FOR EFL LEARNERS: A CONTENT ANALYSIS - Noviana Sari (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2026)
Conversational implicature as a branch of pragmatic science is divided into two, namely Generalized conversational implicature and particularized conversational implicature. This research discusses the implicature contained in the content of the English textbook for grade VII of the independent curriculum. This study aims to explain the types of implicature contained in the content of the English textbook for grade VII of the Merdeka curriculum. The theory used in this study is pragmatic theory. The method used is a qualitative descriptive method. The source of this research data is the content of the English textbook for grade VII of the independent curriculum. The results of this study are the types of conversational implicature, namely Generalized conversational implicature and particularized conversational implicature in the content of the English textbook for grade VII of the independent curriculum.